MEDICINA, EUGENIA E SAÚDE PÚBLICA: JOÃO CANDIDO FERREIRA E UM RECEITUÁRIO PARA A NAÇÃO (1888-1938) - Pietta, Gerson (2015)
This proposal aims to understand the representations of João Candido Ferreira in different fields of social action, in the political field, in the medical field and in the literary field. For that, it uses different historical sources, among them scientific journals, newspapers and literary journals, as well as a biography produced by a medical pro-memory institution, and scientific texts published by the author. This objective contemplates at first an analysis of the fragments of João Candido trajectory, analyzing their movement through the fields, and the trajectory of the individual in relation to the group in its various social fields. Aims to understand the scientific and social movement known as eugenics from the discourse analysis of paranaense doctor João Candido Ferreira, in the article The Eugenic, which according to the author, comes to be the adornment of a series of studies dealing with improving the fate of humanity. It is believed that these texts are formative of his prescription of nation and revels his medical sociography. The study discusses how João Candido Ferreira realized the medicine in society, what was the role of the doctor, and what were his dialogues and conjunctions in relation to eugenics, to sanitation, and the hygienism. It is intended to specifically understand how this thought heredity and eugenics marriage as well as understand how was the use of eugenics and medicine for nation building. The timeline chosen for the analysis is from 1888 to 1938.